Prevalence of gene expression additivity in genetically stable wheat allohexaploids. Issue 3 (21st December 2012) - Chelaifa, Houda; Chagué, Véronique; Chalabi, Smahane; Mestiri, Imen; Arnaud, Dominique; Deffains, Denise; Lu, Yunhai; Belcram, Harry; Huteau, Virginie; Chiquet, Julien; Coriton, Olivier; Just, Jérémy; et al.
Summary: The reprogramming of gene expression appears as the major trend in synthetic and natural allopolyploids where expression of an important proportion of genes was shown to deviate from that of the parents or the average of the parents. In this study, we analyzed gene expression changes in previously reported, highly stable synthetic wheat allohexaploids that combine the D genome of Aegilops tauschii and the AB genome extracted from the natural hexaploid wheat Triticum aestivum . A comprehensive genome‐wide analysis of transcriptional changes using the Affymetrix GeneChip Wheat Genome Array was conducted. Prevalence of gene expression additivity was observed where expression does not deviate from the average of the parents for 99.3% of 34 820 expressed transcripts. Moreover, nearly similar expression was observed (for 99.5% of genes) when comparing these synthetic and natural wheat allohexaploids. Such near‐complete additivity has never been reported for other allopolyploids and, more interestingly, for other synthetic wheat allohexaploids that differ from the ones studied here by having the natural tetraploid Triticum turgidum as the AB genome progenitor. Our study gave insights into the dynamics of additive gene expression in the highly stable wheat allohexaploids.